Prevalence of circulating tumor cells in early breast cancer patients 2 and 5 years after adjuvant treatment - Bauer, Emanuel C. A.; Schochter, Fabienne; Widschwendter, Peter; Degregorio, Amelie; Andergassen, Ulrich; Friedl, Thomas W. P.; Fasching, Peter; Fehm, Tanja; Schneeweiss, Andreas; Beckmann, Matthias; Pantel, Klaus; Janni, Wolfgang; et al. (Breast Cancer Research and Treatment, 2018)
Several studies have provided evidence on the prognostic relevance of circulating tumor cells (CTCs) detected before and after chemotherapy regarding overall survival (OS) and progression-free survival (PFS) in early breast cancer (EBC). We provide data on the prevalence of CTCs 2 and 5 years after primary diagnosis in a cohort of patients with EBC.The SUCCESS study is a multicenter, prospective, randomized trial comparing PFS in primary breast cancer patients undergoing one of two adjuvant chemotherapy regimens followed by 2 versus 5 years of treatment with zoledronate. CTCs from patients without signs of breast cancer recurrence were analyzed in peripheral blood using the FDA cleared CellSearch® System (Veridex, USA) 2 and 5 years after primary diagnosis.CTCs were detected at 2 and 5 years after primary diagnosis in 96 (16.7%) and 47 (8.2%) of the 574 patients, respectively. There were no associations between CTC status and patient and tumor characteristics or treatment regimens. In 442 (77.0%) patients, no CTCs were detected at either of the two time points, and in 11 patients (1.9%), CTCs were found at both 2 and 5 years after primary diagnosis. In 85 (14.8%) patients, CTCs were present 2 years after primary diagnosis but not after 5 years, while 36 (6.3%) patients had CTCs in their blood only at the 5-year follow-up.In patients with EBC, CTCs can be detected even 5 years after primary diagnosis without clinical signs of disease recurrence.
EVALuna2:56145